2010
DOI: 10.1159/000316356
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Varicocele Induces p53-Dependent Germ Cell Apoptosis through Activation of γ-H2AX

Abstract: Aim: Since DNA damage-related apoptosis is raising concerns regarding abnormal spermatogenesis, we investigated the changes in γ-H2AX during testicular germ cell apoptotic responses in the varicocele model. Materials and Methods: Varicocele was induced by partial ligation of the left renal vein and animals were sacrificed at 1, 3, and 4 weeks after varicocele creation. The levels of activated p53 and γ-H2AX formation were determined by Western blot analysis and immunohistochemistry. Results: γ-H2AX formation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…However, this is also a decompensated progress, in which the production of ROS in vivo is beyond the cell antioxidant ability. The intracellular ROS accumulation may damage the protein, DNA and lipid, leading to the impairment of cell functions (Chang et al ., ,b). Carmeliet found that the inducing apoptosis protein p53 would increase in the protecting progress under hypoxia environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is also a decompensated progress, in which the production of ROS in vivo is beyond the cell antioxidant ability. The intracellular ROS accumulation may damage the protein, DNA and lipid, leading to the impairment of cell functions (Chang et al ., ,b). Carmeliet found that the inducing apoptosis protein p53 would increase in the protecting progress under hypoxia environment.…”
Section: Discussionmentioning
confidence: 99%
“…The tumour suppressor protein p53 (p53), first found in tumour tissues, can regulate the cell cycle as a kind of apoptosis‐inducing protein. Excessive expression of p53 will induce apoptosis (Semenza & Wang, ; Kaluzova et al ., ; Chang et al ., ,b; Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…p53, a master gene in apoptosis and a target of p38 MAPK (Figure 2), is activated in rats with experimental varicocele [156]. In fact, the proapoptotic gene Bax, which is a transcriptional target of p53, is upregulated in experimental varicocele in animal models [47, 157159]. In addition, the downregulation of Bcl-2 and increased expression of caspase-9 and activated caspase-3 in the ipsilateral testis at eight and 12 weeks after the onset of varicocele has been documented, indicating gradually increased testicular tissue apoptosis through the intrinsic pathway [158].…”
Section: Local Hypoxia: Varicocele and Testicular Torsionmentioning
confidence: 99%
“…Nuclear factor‐kappa B (NF‐κB), a key regulator of the inflammatory gene, was reported to be involved in varicocele‐induced testicular dysfunction (Tuğcu et al, ). The study in an experimental rat varicocele model implied that P53 mediated apoptosis through activation of γ‐H2AX (Chang, Kim, Park, & Yoon, ). However, the studies in varicocele above mainly focused on known apoptosis‐related proteins, and a comprehensive investigation is still necessary to clarify the mechanism of apoptosis.…”
Section: Discussionmentioning
confidence: 99%